Stresses in Women After Mastectomy - AYESHA SHAUKAT HURRIAT AFZAL, ANDLEEB KHANAM (Journal of Fatima Jinnah Medical University, 2018)
Objectives: To identify and focus on different types of stresses faced by women after mastectomy in our country. What type of life these women live after treatment? Are they fully satisfied? Or stress continues? Presently research done in this respect in our patients is insufficient . Materials and Methods: 50 patients who had mastectomy were included in the study .Patients with metastasis and recurrence were excluded from the study. Data was collected through interviews and the information collected was recorded on a Performa. Results: Stress of recurrence was seen in 84% women, fear of dyeing in 80%, economic problems faced by 68% women, cosmetic concerns in 56%, stress of chemotherapy 49%disability stress in 47%, social factors involved in 24%, family in12% and very strangely stress of husband seen in only 7%.Marital status shows 97% married and only 3% unmarried. widow 5% and divorced3%. Occupation was House wives85%. Health worker-3%, Teacher-4%, Other office jobs.Educational status showed that 40% were illiterate,28% matriculation, Under matric 28% and only one patient masters degree. Conclusion: Different types of stress exists in all women after the treatment and this period needs psychological support through counseling services which is deficient in our setup. So assisting them in obtaining appropriate psychosocial services.